Identifikasi Kesehatan Spiritual Lansia dalam Upaya Pertahanan Imun pada Masa Adaptasi Kehidupan Baru - Muhammad Hidayat; Maimaznah Maimaznah (3031-8572, 2022)
Immunosenescent is the occurrence of changes in immune function due to the effects of aging. This process will affect all cell types and pathways of immune response, both innate and adaptive immune responses. The presence of immunosenescence in the elderly cause’s susceptibility to respiratory tract infections. The principle of preventing the transmission of COVID-19 to individuals is done by avoiding the entry of the virus. In addition to immunosensor and the presence of comorbidities, malnutrition is a very common case in the elderly and also causes a low immune system. One of the characteristics of this phase, usually the elderly contemplates the nature of their lives more intensively and try to get closer to God. spiritual intelligence affects the anxiety of the elderly in the face of death. Elderly with a high spiritual level do not feel anxious about death. The general objective of this study is to identify the spiritual health of the elderly in an effort to maintain immunity during the adaptation period to a new life. This study uses a qualitative descriptive research method with a phenomenological approach. The results of this study are the relationship between the elderly and others at a high spiritual level as many as 32 out of 42 (76.2 %), the elderly relationship with oneself is at a moderate spiritual level as many as 25 out of 42 (59.5 %), the relationship between the elderly and the natural surroundings are at a high spiritual level as many as 31 out of 42 (73.8 %), the elderly's relationship with God is at a high spiritual level as much as 28 out of 42 (66.7 %). The conclusion of this study is the spiritual health of the elderly in an effort to maintain immunity during the adaptation period to a new life at a high spiritual level.